Use of Information and Communication Technology in Virtual Laboratory Use Instructions - Bonok, Zainudin; Lakoro, Fitriani; Junus , Alya Pratiwi Putri (East Asian Journal of Multidisciplinary Research, 2024)
This project aims to enhance the Basic Telecommunications Engineering practicum by leveraging advancements in information and communication technology through digital transformation. The virtual lab addresses challenges such as limited equipment availability and obstacles preventing physical attendance, allowing practicums to be conducted remotely and on schedule. The virtual lab not only supports students in completing their practicum regardless of location and time constraints but also aims to improve the quality of education. Students must register with a username and password to access the Digital Transformation Practicum. Future developments include web-based practicum opportunities, further expanding online education for the course. Research indicates that, with a stable internet connection, virtual laboratory technology can be sustainably utilized to benefit students' learning experience.